Ayurvedic perspective of dietary risk factors of colorectal cancers - A hospital-based case control study - Sadanand Sardeshmukh; Vineeta Deshmukh; Vasanti Godse; Shweta Gujar; Sneha Dalvi; Swapna Kulkarni; Sushama Bhuvad; Nilambari Sardeshmukh; Bhagyashree Sardeshmukh; Dhananjay Deshpande; Vinita Awalkanthe; Amruta Salunkhe; et al. (Journal of Ayurveda and Integrative Medicine)
Background: The rising prevalence of colorectal cancer (CRC) may be attributed to various nutritional and behavioural factors, making both factors as important topics for discussion to the layman and the oncology community. Objective: To explore additional dietary risk factors, other than those already known, according to the Ayurvedic perspective in CRC patients. Methods: Detail dietary data was collected from 420 patients of CRC and 116 healthy volunteers registered at our institute with the help of a food frequency questionnaire. Descriptive analysis was done by plotting radar charts, whereas the logistic regression models were used to calculate the adjusted Odd Ratios (ORs) associated with consumption of green chilli, red chilli powder and curd, individually and in combinations. Results: The controls in the present study were younger, had more males, the majority of them belonged to middle- and lower-income groups and had a family history of cancer as compared with cohort of case studies. Green chilli consumption was found to be the maximum within the lower-income group (n = 18, 66.67%), while that of red chilli (n = 150, 48.23%), and curd (n = 107, 34.04%) within the middle class. Maximum consumption of green chillies (Males n = 48, 29.27%; Females n = 36, 21.95%), red chillies (Males n = 40, 29.85%; Females n = 16, 24.61%) and curd (Males n = 31, 28.97%) was observed in the age group 46 to 60 irrespective of sex. Tobacco was found to be the most common addiction in all groups. The maximum number of patients frequently consuming these three dietary items presented majorly with rectal cancer, and liver metastasis and were in advanced grade and stage of cancer. Curd and curd with red chilli powder had a significant association with the development of CRC with an OR of 2.7280 (95% CI 1.6346 to 4.5531) and 5.0806 (95% CI 2.4015 to 10.7485), respectively, which was highly significant (p < 0.0001). Green chilli was notably an associated risk with an OR of 2.0095 (95% CI 1.3258 to 3.0458), which was also statistically significant (p = 0.001). Red chilli powder and green chilli with curd had ORs as 1.6917 (95% CI 1.1105 to 2.5771) and 2.1778 (95% CI 1.1591 to 4.0918) with p = 0.0144 and 0.0156, respectively. Conclusion: In the present study, green chilli, red chilli, and curd are identified as additional dietary risk factors for colorectal cancers, owing to their ability to produce chronic inflammation leading to various inflammatory conditions including cancer.